Strategi Pemberdayaan Ekonomi Masyarakat Berbasis Komoditi Lokal Di Kabupaten Sintang - Yunita Astikawati; Kardius Richi Yosada; Munawar Thoharudin; Dominggus Sore (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2021)
The progress of the economy in Sintang Regency, one of which is very dependent on community empowerment in moving the wheels of the economy. Where people do not depend on the government for welfare. The government has carried out human resource empowerment programs. Human resource empowerment programs have been carried out by the government. This is in line with Indonesia's development goals, namely to build Indonesian people as a whole, so development must be a social change that does not only occur in the standard of living of the people but also in the role of the elements in it. This study aims to provide an overview of the right strategy as a form of local commodity-based community economic empowerment in Sintang Regency. The research method used in this study is a qualitative descriptive method with a research sample of three sub-districts using a purposive sampling technique The research results are divided into three, namely: the potential for economic development is found in agriculture and plantations; business opportunities from agricultural and plantation products can be processed into snacks that have a selling value and are in demand by the community; community economic empowerment strategy with Usaha Ekonomi Produktif (UEP) programs